Counselling agent in online game design for excessive and addictive gaming control - Ididi, Italumeh Okpakhomhe; Hassan, Sa’adah; Abd Ghani, Abdul Azim; Mohd Ali, Norhayati (Faculty of Electronic and Computer Engineering, Universiti Teknikal Malaysia Melaka, 2017)
The issue of online game effects such as excessive play and addiction has attracted the attention of researchers, Government authorities and even stakeholders. For example, Chinese government has adopted daily shutting down of internet cafe at specified hours, and Australian authority enforced censoring certain portion of certain games before they are released. As an effort to tackle this issue, researchers have proposed adopting design changes on time limit as well as providing referral services as ways of limiting harm. The impart of the above are yet to make any remarkable impact on players. In this paper, we proposed a Counseling Agent model integrating informative and self-appraisal messages in online game design as a control measure. Counseling being a major source of addressing most human disorder has become a focus of attraction in addressing the issue of online game overuse in the society. In addition, the informative and self-appraisal messaging in games have proven optimistic through making positive impact on player's thoughts and behavior towards gaming. These messages are expected to remind players about the negative impact of excessive and addictive gaming habits, as well as suggesting possible reductive solutions through message streaming.